The Stereotype of Indo-Chinese Portrayed in Ernest Prakasa’s Stand-up Comedy Material - Sihombing, Lambok Hermanto (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2025)
Stand-up comedy has emerged as a dynamic medium within the media industry, capturing the interest of both comedians and audiences alike. In Indonesia, it serves not only as a form of entertainment but also as a cultural platform to reflect and critique various social issues—one of which is ethnicity. This study explores how Indo-Chinese identity is represented in the stand-up comedy material of Ernest Prakasa, a prominent Indonesian comedian of Chinese descent. Employing Van Dijk’s critical discourse analysis, this qualitative research examines the ways in which ethnic stereotypes are constructed, negotiated, and commodified through humor. The data is drawn from Prakasa’s performance titled “Gua Ernest dan Gua Cina”, as broadcast on the KompasTV YouTube channel. The findings reveal that humor in Indonesian stand-up comedy functions beyond mere entertainment; it also operates as a cultural commodity that both reinforces and challenges ethnic stereotypes. Specifically, Ernest strategically uses self-deprecating humor and irony to normalize Indo-Chinese identity in the public sphere while simultaneously critiquing the underlying prejudices. This dual function of humor suggests that stand-up comedy can serve as a subtle yet powerful tool for social commentary and ethnic negotiation in contemporary Indonesian society.